2011
DOI: 10.1103/physrevb.83.205116
|View full text |Cite
|
Sign up to set email alerts
|

Chiral spin liquid in a correlated topological insulator

Abstract: In this paper, we investigate the topological Hubbard model -the spinful Haldane model with onsite interaction on honeycomb lattice with spin rotation symmetry by using slave-rotor approach and find that chiral spin liquid exists in such a correlated electron system of the intermediate coupling region. By considering the anyon nature of excitations, chiral spin liquid may be the ground state of the topological Hubbard model. The low energy physics is basically determined by its Chern-Simons gauge theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 42 publications
3
70
3
Order By: Relevance
“…Being hard to tackle, some of the previous studies used static mean-field approximations. [13][14][15][16][17] All these studies reported an additional phase with coexisting antiferromagnetic long-range order and non-trivial topological character at intermediate interaction strengths. This topologically non-trivial AFI state has a clear mean-field picture: in the vicinity of a putative second order quantum phase transition to the AFI, the antiferromagnetic order parameter increases continuously so that there is a finite region where the topological band gap persists despite of the counteracting topologically trivial band gap due to the magnetic order.…”
Section: -10mentioning
confidence: 99%
See 1 more Smart Citation
“…Being hard to tackle, some of the previous studies used static mean-field approximations. [13][14][15][16][17] All these studies reported an additional phase with coexisting antiferromagnetic long-range order and non-trivial topological character at intermediate interaction strengths. This topologically non-trivial AFI state has a clear mean-field picture: in the vicinity of a putative second order quantum phase transition to the AFI, the antiferromagnetic order parameter increases continuously so that there is a finite region where the topological band gap persists despite of the counteracting topologically trivial band gap due to the magnetic order.…”
Section: -10mentioning
confidence: 99%
“…Both static mean-field calculations [13][14][15][16][17] and CDMFT on 2-site clusters 33 predict a continuous phase transition from CI to the AFI, with an intermediate topologically non-trivial AFI phase for a wide range of λ. Also results of a variational cluster approximation calculation on 6-site clusters 33,40 indicate an indirect transition from CI to AFI, but via a topologically non-trivial non-magnetic insulating phase with opposite Chern number as the CI.…”
Section: Comparison To Small Cluster Calculationsmentioning
confidence: 99%
“…Therefore, studying its effects on the transport coefficients is of fundamental importance for the next generation of cold atom experiments. So far, the properties of the Haldane-Hubbard model have been investigated mostly via mean-field, variational and numerical analyses [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we need to point out that the Kane-Mele model [3] or the spinful Haldane model [14] with fluxsuperlattice exhibit similar topological features. Due to the spin degree of freedom, a π-flux on the these models traps two zero models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%